2021
DOI: 10.1016/j.fct.2021.112161
|View full text |Cite
|
Sign up to set email alerts
|

The effects of some essential and toxic metals/metalloids in COVID-19: A review

Abstract: Thousands of studies have been conducted in order to understand in depth the characteristics of the novel coronavirus SARS-CoV-2, its infectivity and ways of transmission, and very especially everything related to the clinical and severity of the COVID-19, as well as the potential treatments. In this sense, the role that essential and toxic metals/metalloids have in the development and course of this disease is being studied. Metals/metalloids such as arsenic, cadmium, lead, mercury or vanadium, are elements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 95 publications
1
26
0
2
Order By: Relevance
“…Recent studies have demonstrated the efficiency of selenium supplementation in viral infections such as polio, influenza, HIV, hantavirus, and SARS-CoV [14,47,48]. The decreased level of selenium among COVID-19 patients and its association with severity and mortality of disease may suggest the application of selenium supplementation for COVID-19 cases, but it has not been proven yet in large-scale clinical trials [4,11,49]. There is a narrow range between an appropriate and a toxic amount of this metalloid, so selenium supplements should be taken with caution [50].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the efficiency of selenium supplementation in viral infections such as polio, influenza, HIV, hantavirus, and SARS-CoV [14,47,48]. The decreased level of selenium among COVID-19 patients and its association with severity and mortality of disease may suggest the application of selenium supplementation for COVID-19 cases, but it has not been proven yet in large-scale clinical trials [4,11,49]. There is a narrow range between an appropriate and a toxic amount of this metalloid, so selenium supplements should be taken with caution [50].…”
Section: Discussionmentioning
confidence: 99%
“…With a lack of some trace elements, human immunity decreases, in the case of compensation with heavy metals, a negative effect on the body is also observed. The current SARS-CoV-2/COVID-19 epidemic has had a significant impact on the health of citizens (Domingo & Marquès, 2021 ). Consideration should be given to the role of metals and metalloids in the treatment of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the trace elements, cobalt is closely associated with human health [6]. Cobalt is essential to the metabolism of all animals due to its key role in cobalamin, also known as vitamin B12, the primary biological reservoir of cobalt as an ultra-trace element.…”
Section: Introductionmentioning
confidence: 99%